Community Structure and Genetic Diversity of Dominant Riparian Vegetation Species in the Kedung Ingas River Following Sand Mining Activities - Budi Setiadi Daryono; Abdul Razaq Chasani; Nidianti, Esty (Berkala Ilmiah Biologi, 2026)
Riparian ecosystems play a crucial role in maintaining river ecological functions but are highly vulnerable to anthropogenic disturbances, including sand mining. Sand mining activities in the Kedung Ingas River, Cilegon City, have altered habitat conditions and riparian vegetation structure. This study aimed to evaluate the structure, composition, and genetic diversity of dominant riparian vegetation species following sand mining activities using an integrated ecological and molecular approach based on Inter Simple Sequence Repeat (ISSR) markers. The study was conducted across three riparian zones representing a disturbance gradient: upstream (non-mining), middle (post-sand mining), and downstream (deposition zone). In each zone (±100 m), two observation sites were established (six sites in total), and three plots were set up at each site: 5 m x 5 m (trees), 2 m x 2 m (saplings), and 1 m x 1 m (seedlings). Vegetation structure and composition were analyzed using the Important Value Index (IVI), while community diversity was assessed using the Shannon–Wiener, Simpson, and evenness indices. Seedling community patterns were further examined using Non-metric Multidimensional Scaling (NMDS). Genetic analysis was performed on three dominant species, Swietenia macrophylla, Microcos paniculata, and Musa sp., using five ISSR primers. The results showed that riparian vegetation comprised 28 species from 19 families, with the highest diversity observed in the seedling stratum. The post-mining zone was dominated by pioneer species, whereas the downstream zone indicated secondary succession. ISSR analysis generated a total of 29 loci, with PIC values ranging from 0.26 to 0.44 and polymorphic loci ranging from 60% to 100%, indicating moderate to high levels of genetic diversity. These findings suggest that dominant riparian vegetation still retains sufficient genetic diversity to support natural regeneration and ecosystem restoration following sand mining.